Kualitas Hubungan Interpersonal Pada Pengalaman Individu Toxic Relationship - Safinatunnaja; Wahyuni, Indah Noor; Mareti, Vivitia; Anjani, Putri Nor (Program Studi Psikologi Islam, 2025)
Abstract This study aims to examine the quality of interpersonal relationships among young adults who have experienced toxic relationships, focusing on trust, sincerity, empathy, and communication. Using a qualitative approach, interviews and observations were conducted with four participants aged 20–25 who had been victims of toxic relationships. The findings reveal that such experiences have a significant impact on their capacity to build healthy relationships. Regarding trust, all participants reported a breakdown and became more selective in self‑disclosure. Sincerity was shaped by past experiences and expressed through the way individuals treat others. Empathy emerged through emotional regulation and the provision of social support, while interpersonal communication was mainly practiced with peers deemed safe and supportive. Thus, toxic relationship experiences deeply influence interpersonal patterns, and recovery occurs gradually through emotional support within secure relationships. These results can inform psychological interventions aimed at helping individuals rebuild adaptive and healthy interpersonal connections after relational trauma. Abstrak Penelitian ini bertujuan mengkaji kualitas hubungan interpersonal pada individu dewasa awal yang pernah mengalami toxic relationship dengan fokus aspek kepercayaan, ketulusan, empati, dan komunikasi. Penelitian menggunakan pendekatan kualitatif dengan metode wawancara dan observasi terhadap empat partisipan berusia 20–25 tahun yang menjadi korban toxic relationship. Hasil penelitian menunjukkan, pengalaman hubungan toksik berdampak signifikan pada kemampuan individu membangun relasi sehat. Pada aspek kepercayaan, seluruh partisipan mengalami keruntuhan kepercayaan dan cenderung selektif dalam membuka diri. Ketulusan dipengaruhi pengalaman masa lalu dan muncul melalui cara individu menyikapi orang lain. Aspek empati ditunjukkan pengelolaan emosi dan dukungan sosial, sementara komunikasi interpersonal dilakukan teman sebaya yang dianggap aman dan suportif. Jadi, pengalaman toxic relationship memengaruhi pola hubungan interpersonal secara mendalam, dan pemulihan bertahap melalui dukungan emosional dengan relasi yang aman. Hasil ini dapat menjadi dasar intervensi psikologis untuk mendukung individu membangun hubungan interpersonal adaptif dan sehat pasca trauma relasi.